The Influence of Past Metronidazole Exposure on the Outcome of Helicobacter pylori Eradication - Younghee Choe; Joon Sung Kim; Hyun Ho Choi; Dae Bum Kim; Jae Myung Park; Jung Hwan Oh; Tae Ho Kim; Dae Young Cheung; Woo Chul Chung; Byung-Wook Kim; Sung Soo Kim (Frontiers in Microbiology, 2022)
BackgroundBismuth quadruple therapy (BQT) is recommended as empirical first-line therapy because it is not affected by antibiotic resistance. We examined whether past exposure to metronidazole affected BQT outcomes.MethodsThe records of seven hospitals were searched for patients who received BQT for Helicobacter pylori eradication between 2009 and 2020. The association between past metronidazole exposure and the eradication rate was evaluated.ResultsThis study was a multicenter retrospective study. Around 37,602 people tested for H. pylori infection were identified, and 7,233 received BQT. About 2,802 (38.7%) underwent a 13C-urea breath test to confirm eradication. The BQT efficacy was 86.4% among patients without metronidazole exposure and 72.8% among patients with exposure (p < 0.001). The eradication rate of BQT 14 days in patients with past exposure was higher than that of BQT <14 days (85.5 vs. 66.0%, p = 0.009). Multivariate analysis revealed that past metronidazole exposure [odds ratio (OR) 2.6, 95% CI 1.8–3.7; p < 0.001] and BQT <14 days (OR 1.5, 95% CI 1.2–2.0; p = 0.002) were independent risk factors for eradication failure.ConclusionPast metronidazole exposure significantly lowered the BQT eradication rate. BQT 14 days should be recommended for patients with suspected metronidazole exposure.